Using Picture Series to Inspire Reading Comprehension for the Second Semester Students of English Department of IAIN Tulungagung - Nurhayati, Dwi Astuti Wahyu (Dinamika Ilmu, 2014)
The problem highlighted in this research is the low reading comprehension of the second semester students of English Department in State College of Islamic Studies Tulungagung that is caused by (a) the uninteresting activities in reading class; (b) the students difficulties in understanding and retelling the ideas of the text; (c) the students low motivation in reading habit. The theoretical review includes the nature of reading, picture series, inspiring reading, and the nature of motivation. The procedure of the research consists of identifying the problem, planning the action, implementing the action, observing the action, and reflecting the result of the research. In this research, the researcher acts as the lecturer who conducts the action research in the classroom and she is helped by her collegues. In collecting the data, the researcher uses observational technique supported with tests. In analysing the data, it was used t-test non independent, the researcher uses the observation, questionaire, interview, students âwork supported with the video recording and photograph,then also compares the result of the students pre-test and post-test to answer the research questions. There is significant improvement in the result of pre-test and post-test of cycle 1 and 2. In cycle 1, t0 (6.89766) is higher than tt (1.73) and in cycle 2, t0 (10.8622) is also higher than tt (1.73). From these two results, therefore, h0 is rejected and the alternative hypothesis (ha) is accepted. By retelling the ideas and summarizing the text using interesting media especially picture series can increase the students motivation in reading class especially to improve their reading comprehension.